THE EFFECT OF ANIONIC AND NONIONIC CO-SURFACTANT FOR IMPROVING SOLUBILITY OF POLYOXY-BASED SURFACTANT FOR CHEMICAL FLOODING - Yani Faozani Alli; Dadan Damayandri; Yan Irawan (Testing Center for Oil and Gas LEMIGAS, 2017)
Surfactant is one of the crucial components for chemical flooding to recover oil production in the tertiary stage of the low primary and secondary recovery oil field. The mechanism is performed by decreasing the interfacial tension of oil and water which enhancing microscopic displacement efficiency. The present study showed the effect of commercial nonionic and anionic co-surfactant Tergitol, Teepol, Merpol, and SDS on the solubility of polyoxy based-surfactant (POS) through compatibility analysis, fi ltration ratio analysis, and IFT measurement. Whereas the presence of Teepol and Merpol did not change the original compatibility of POS in all concentrations, the addition of co-surfactant Tergitol and SDS were able to alter the solubility of POS from milky solution into a clear transparent solution. However, the most important characteristic of surfactant for reducing the IFT of oil-water was affected by the addition of co-surfactant which does not have sufficient IFT to release the trapped oil in the reservoir. Thus, exposing the mixture of surfactant and co-surfactant for a few days at the reservoir temperature has changed the visual appearance of solution from a clear transparent solution into a milky suspension, indicating the occurrence of thermal degradation. These results suggest that the addition of anionic and nonionic co-surfactant improved the solubility of POS, but increased the IFT. It can be concluded that the compatibility of POS in the brine can then be achieved by mixing it with suitable co-surfactant. Screening the other co-surfactant is required to obtain the one that enhances the compatibility as well as maintaining the ultralow IFT of POS.